Synthesis of High Aspect-Ratio Gold Nanowires with Highly Porous Morphology. (18th June 2012) - Johnson, Lucas P.; Matisons, Janis G.
Abstract : Here, we demonstrate the formation of porous gold nanowires with diameters <60 nm by a two-step process involving the successive electrodeposition of silver then gold into the pores of a track-etched polycarbonate filtration membrane, followed by treatment with nitric acid. The resulting nanowires possess a unique, highly porous morphology, which yields a very high accessible surface area to volume ratio compared to solid nanowires of the same dimensions. Combined with the high aspect ratio of these particles (which allows for easy isolation from solution), this makes them eminently suitable for use in catalysis and sensing applications. The formation of such porous gold nanostructures was ascertained to result from the low diffusivity of the silver species within the narrow membrane pores.